CRISPR/Cas genome editing system and its application in potato - Hou, Xin; Guo, Xiaomeng; Zhang, Yan; Zhang, Qiang (Frontiers in Genetics, 2023)
Potato is the largest non-cereal food crop worldwide and a vital substitute for cereal crops, considering its high yield and great nutritive value. It plays an important role in food security. The CRISPR/Cas (clustered regularly interspaced short palindromic repeats/CRISPR-associated) system has the advantages of easy operation, high efficiency, and low cost, which shows a potential in potato breeding. In this paper, the action mechanism and derivative types of the CRISPR/Cas system and the application of the CRISPR/Cas system in improving the quality and resistance of potatoes, as well as overcoming the self-incompatibility of potatoes, are reviewed in detail. At the same time, the application of the CRISPR/Cas system in the future development of the potato industry was analyzed and prospected.